PELATIHAN RAGAM AKTIVITAS MELUKIS YANG MENYENANGKAN BERSAMA ANAK USIA DINI DI KELOMPOK BERMAIN NURUL HIDAYAH - Ramadani, Cepi; Husni, Jaelani; Ainun, Siti (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2024)
This community service is carried out because, in the school where this service takes place, children tend to feel bored when coloring activities are less varied. Not a few children don't want to color because of the lack of a variety of fun drawing activities with children. This community service introduces schools to a variety of fun painting activities with children, including painting using paint and straws, and painting using paint and thread. The method used in this study is to use demonstrations and then practice directly. As for the results of this community service, both children, teachers, and parents were very enthusiastic about participating in this activity. Children feel happy and excited because children can explore their imagination through this painting activity. In addition, the children were very interested because this was the first time they had done a painting activity using paint and straws, and cans with thread. As a reflection, teachers and parents must be more creative in making various activities at school or home, because children are very interested in new things.